Implementing web-based ping-pong-type e-communication to enhance staff satisfaction, multidisciplinary cooperation, and clinical effectiveness: A SQUIRE-compliant quality-improving study. Issue 44 (November 2016) - Yeh, Pei-Han; Hung, Shih-Kai; Lee, Moon-Sing; Chiou, Wen-Yen; Lai, Chun-Liang; Tsai, Wei-Ta; Hsieh, Hui-Ling; Shih, Yi-Ting; Chen, Liang-Cheng; Huang, Li-Wen; Lin, Yi-An; Lin, Po-Hao; et al.
Abstract: Background: Frequent multidisciplinary communication is essential in conducting daily radiotherapy (RT) practice. However, traditional oral or paper-based communication has limitations. E-communication has been suggested, but its effects are still not well demarcated in the field of radiation oncology. Objects: In our web-based integrated information platform, we constructed a ping-pong-type e-communication function to transfer specific notations among multidisciplinary RT staffs. The purpose was to test whether applying this e-communication can increase effectiveness of multidisciplinary cooperation when compared with oral or paper-based practice. Staff satisfaction and clinical benefits were also demonstrated. Design and setting: A real-world quality-improving study was conducted in a large center of radiation oncology. Participants and dataset used: Before and after applying multidisciplinary e-communication (from 2014 to 2015), clinical RT staffs were surveyed for their user experience and satisfaction ( n = 23). For measuring clinical effectiveness, a secondary database of irradiated head and neck cancer patients was re-analyzed for comparing RT toxicities ( n = 402). Interventions: Applying ping-pong-type multidisciplinary reflective e-communication was the main intervention. Outcome measures: For measuring staff satisfaction, eight domains were surveyed, such as timeliness, convenience, and completeness. For measuring clinical effectiveness of multidisciplinary cooperation, event rates of severe (i.e., grade 3–4) RT mucositis and dermatitis were recorded. Results: Overall, when compared with oral communication only, e-communication demonstrated multiple benefits, particularly on notation-review convenience (2.00 ± 1.76 vs 9.19 ± 0.81; P < 0.0001). When compared with paper-based practice, e-communication showed statistically significant benefits on all eight domains, especially on notation-review convenience (5.05 ± 2.11 vs 9.19 ± 0.81; P < 0.0001) and convenience of feedback notation (4.81 ± 1.72 vs 8.76 ± 1.09; P < 0.0001). Moreover, staff satisfaction was gradually increased from oral (3.57 ± 1.94), paper-based (5.57 ± 2.06), to e-communication (8.76 ± 0.70; P < 0.0001). Secondary measurement confirmed these observations. Before and after facilitating multidisciplinary cooperation by using e-communication, severe (i.e., grade 3–4) mucositis and dermatitis were decreased from 21.7% to 10% then to 5.1%. Conclusions: Replacing oral or paper-based practice with e-communication is useful in facilitating RT multidisciplinary teamwork. Staff satisfaction and clinical effectiveness can be increased.